Which program for whom? Evidence on the comparative effectiveness of public sponsored training programs in Germany - Martin Biewen; Bernd Fitzenberger; Aderonke Osikominu; Marie Waller (Institute for the Study of Labor (IZA), 2007)
We use a new and exceptionally rich administrative data set for Germany to evaluate the employment effects of a variety of public sponsored training programs in the early 2000s. Building on the work of Sianesi (2003, 2004), we employ propensity score matching methods in a dynamic, multiple treatment framework in order to address program heterogeneity and dynamic selection into programs. Our results suggest that in West Germany both short-term and medium-term programs show considerable employment effects for certain population subgroups but in some cases the effects are zero in the medium run. Short-term programs are surprisingly effective when compared to the traditional and more expensive longer-term programs. With a few exceptions, we find little evidence for significant positive treatment effects in East Germany. There is some evidence that the employment effects decline for older workers and for low-skilled workers.
Keywords: 330; Arbeitsmarktpolitik; Weiterbildung; Wirkungsanalyse; Beschäftigungseffekt; Deutschland